Factors Affecting Browning of Sago (Metroxylon Sagu Rottb.) Pith and Their Effects on Sago Starch - Anthonysamy, Shirlene Maria (2002)
The effect of four parameters on the browning of sago pith was evaluated i.e. maturity of the sago palm, and holding time, pH and temperature of the sago pith slurry. The effect of sago palm maturity on the browning of sago pith was determined using sago pith slurries from three maturity stages i.e. young, premature and mature. The sago palms were sectioned into top and bottom to examine the effect of trunk growth on the concentrations of soluble phenolic compounds. Two soluble phenolic compounds were found to be present in the sago pith i.e. (+)-catechin and (-)-epicatechin. Concentrations of (+)-catechin and (-)-epicatechin were higher in mature sago palms while distribution of these compounds with trunk gowth did not show a clear correlation. Soluble polyphenol oxidase (SPPO) activity increased while latent polyphenol oxidase (LPPO) activity decreased with increase in maturity of the sago palms. Colour development in the slurry monitored in terms of lightness (L) and redness (a) using the HunterLab Ultrascan Spectrocolorimeter was more intense (darker and redder) in mature sago palms.The effect of holding time, pH and temperature of the sago pith slurry was studied using a mature sago palm. Browning was evaluated based on concentrations of (+)-catechin and (-)-epicatechin and colour development in the sago pith slurry. The effect of holding time (duration for which sago pith slurries were held) on the browni ng of sago pith slurry was studied for 1, 6, 12 and 24 hours. An increase in holding time resulted in significant (P<0.05) decreases of (+)-catechin and (-)-epicatechin. Colour development in the slurry was significantly (P<0.05) more intense with increased holding time but was not significant (P<0.05) after six hours. The effect of pH on the browning of sago pith was studied using sago pith slurries with pH from 3.5 to 7.0 with a holding time of 24 hours. Concentrations of (+)-catechin and (-)-epicatechin decreased significantly (P<0.05) with an increase in pH particularly between pH 5.0 and 6.5 which resulted in significant (P<0.05) colour development. The effect of temperature on the browning of sago pith was investigated using sago pith slurries with temperatures from 10°C to 50°C with a holding time of 24 hours . The amount of (+)-catechin and (-)-epicatechin decreased significantly (P<0.05) with the increase in temperature while colour development increased significantly (P<0.05) with temperatures particularly above 40°C. The quality of sago starch extracted from slurries with different pH and temperatures and held for 24 hours was determined. Starch quality was determined in terms of colour development, granule morphology and pasting profile. Significant (P<0.05) colour development was noted in starches extracted from slurries of different pH and temperatures though they were washed twice during extraction. Granule morphology of the starches was observed using the Scanning Electron Microscope. Starches from slurries of strong acidic (pH 3.5 to 4.5) conditions exhibited fissures on the surface of granules while those from weaker acidic (pH 5.0 to 7.0) conditions had minor protrusions. Starches from slurries at different temperatures had only minor modifications on the surface of the granules. The pasting profile of the starches was examined using the Brabender Viskograph. Starches from strong acidic conditions showed lower viscosities while starches from high temperatures (30°C to 50°C) were not greatly affected.